The Impact of Parenting on Adolescent Aggression: A Psychological and Social Review - VB, Devapramod (Yayasan Sinergi Kawula Muda, 2024)
Adolescent aggression is a significant public health concern, often influenced by parenting styles and broader socio-environmental factors. This study examines the relationship between parenting practices and adolescent aggression, emphasizing the effects of warm versus harsh parenting. Utilizing a systematic narrative review, literature was sourced from databases including Scopus, PubMed, and Web of Science, employing specific inclusion criteria to ensure the reliability of findings. The results indicate that supportive and authoritative parenting styles contribute to lower aggression levels, whereas harsh and neglectful parenting increase the likelihood of aggressive behaviors. Additionally, parental mental health, socio-economic stressors, and peer influences play critical roles in shaping adolescent aggression. The discussion highlights the necessity of policy interventions focusing on parental education, mental health support, and structured community programs to mitigate aggressive tendencies in adolescents.These findings emphasize the importance of a holistic approach that integrates psychological, social, and economic perspectives to develop effective interventions. Future research should prioritize longitudinal studies, cross-cultural comparisons, and community-based intervention assessments to provide a more comprehensive understanding of the factors influencing adolescent aggression. Addressing these challenges through a multi-pronged strategy can contribute to more effective policies and improved adolescent behavioral outcomes.